2003
DOI: 10.1074/jbc.m306068200
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Active Site Alterations upon Mutation of Yeast Pyruvate Kinase Using 205Tl+ NMR

Abstract: Yeast pyruvate kinase (YPK) 1 (EC 2.7.1.4.0) is a tetrameric enzyme of identical subunits with a subunit molecular mass of 54.5 kDa (1). PK is a key regulatory enzyme in glycolysis that catalyzes the nearly irreversible reaction of phosphoenolpyruvate (PEP) and ADP to yield pyruvate and ATP. YPK has an absolute requirement for both monovalent and divalent cations, undergoes homotropic activation by PEP and M 2ϩ , and heterotropic activation by fructose 1,6-bisphosphate (FBP). Potassium is the physiologically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Hence, replacement of the hydroxyl functional group with a thiol group on the residue at position 298 may result in conformational changes around the bound PEP substrate in the active site. The T298C mutation does introduce significant conformational alterations of the substrate and the cations at the active site of YPK, as measured by 205 Tl + NMR (25). The interaction of FBP with the fully ligated kinetic complex of YPK is also affected by the T298C mutation (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…Hence, replacement of the hydroxyl functional group with a thiol group on the residue at position 298 may result in conformational changes around the bound PEP substrate in the active site. The T298C mutation does introduce significant conformational alterations of the substrate and the cations at the active site of YPK, as measured by 205 Tl + NMR (25). The interaction of FBP with the fully ligated kinetic complex of YPK is also affected by the T298C mutation (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…Hinton and coworkers have reported chemical shifts for complexed 205 Tl-(I) between -700 and 300 ppm (11) and chemical shift anisotropies of up to 855 ppm (12). Previous NMR studies have demonstrated that the chemical shifts observed by 205 Tl NMR may be powerful probes for the investigation of protein binding sites (13,14) and conformational changes (15,16). Furthermore, 205 Tl longitudinal relaxation times, T 1 , have been examined and used as a means to obtain structural information (17).…”
mentioning
confidence: 99%
“…When oxalate was used as the anion instead of carbonate, the 205 Tl NMR signals originating from the bound metal ion in the sites of ovotransferrin were shifted downfield and became almost degenerate [359]. Conformational changes in wild-type and mutant forms of yeast pyruvate kinase have been investigated by 205 Tl NMR [360,361]. 205 Tl NMR methods have also been developed for the characterisation of monovalent cation binding to nucleic acids, including the first 1 H- 205 Tl scalar couplings observed in a biological system [362].…”
Section: Thalliummentioning
confidence: 99%